Primary Care Physician Designation and Response to Clinical Decision Support Reminders - Weinfeld, Jeffrey M.; Gorman, Paul N. (Applied Clinical Informatics, 2016)
Clinical decision support (CDS) has been shown to improve process outcomes, but overalerting may not produce incremental benefits. We analyzed providers’ response to preventive care reminders to determine if reminder response rates varied when a primary care provider (PCP) saw their own patients as compared with a partner’s patients. Secondary objectives were to describe variation in PCP identification in the electronic health record (EHR) across sites, and to determine its accuracy.We retrospectively analyzed response to preventive care reminders during visits to outpatient primary care sites over a three-month period where an EHR was used. Data on clinician requests for reminders, viewing of preventive care reminders, and response rates were stratified by whether the patient visited their own PCP, the PCP’s partner, or where no PCP was listed in the EHR. We calculated the proportion of PCP identification across sites and agreement of identified PCP with an external standard.Of 84,937 visits, 58,482 (68.9%) were with the PCP, 10,259 (12.1%) were with the PCP’s partner, and 16,196 (19.1%) had no listed PCP. Compared with PCP partner visits, visits with the patient’s PCP were associated with more requested reminders (30.9% vs 22.9%), viewed reminders (29.7% vs 20.7%), and responses to reminders (28.7% vs 12.6%), all comparisons p<0.001. Visits with no listed PCP had the lowest rates of requests, views, and responses. There was good agreement between the EHR-listed PCP and the provider seen for a plurality of visits over the last year (D = 0.917).A PCP relationship during a visit was associated with higher use of preventive care reminders and a lack of PCP was associated with lower use of CDS. Targeting reminders to the PCP may be desirable, but further studies are needed to determine which strategy achieves better patient care outcomes.primary care physician (PCP), clinical decision support (CDS), electronic health record (EHR), National Provider Identifier (NPI)
Keywords: Primary health care; clinical decision support systems; electronic health records